Analisis Pengaruh Perencanaan Sumber Daya Manusia Terhadap Produktivitas Kerja Karyawan PT. Telkom Divisi Acces Kota Lhokseumawe - Yusnidar Yusnidar; Darmawan Darmawan (Sekolah Tinggi Ilmu Administrasi Nasional, 2021)
Human resource is one of the concerns that the government must consider seriously. Human resources, in this case, are a decisive factor for the company's progress because employees play an essential role in achieving company goals, so quality human resources are a resource that has the potential to be developed for the improvement of the corporation. This study sought to determine the effect of human resource planning on the work productivity of Telkom enterprise employees. This research was conducted at the Telkom office in Lhokseumawe City, Indonesia. The number of samples in this study was 30. The survey results simultaneously show that age, education, work experience, and skills increase this company's work productivity. While the results of the partial research also show that age, education, work experience, and abilities affect increasing work productivity. This study suggests that leaders should play an active role in providing role models to employees in carrying out their daily work activities. Thus, it will become a solid work culture that can affect the increase in work productivity in the future. It will also result in a solid work culture that can affect the increase in work productivity